2020
DOI: 10.1021/acs.macromol.0c01605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthesis Temperature on Size, Structure, and Volume Phase Transition of Polysaccharide Microgels

Abstract: High-molecular-weight polysaccharide microgels were synthesized at a range of temperatures above the polymer lower critical solution temperature (LCST) (ΔT = 0.6–18.1 °C), and ΔT was found to strongly influence the structure, dynamics, and volume phase transition temperature of the resulting particles. Static and dynamic light scattering studies and mean field theory analysis of the microgels below and above volume phase transition revealed several distinct regimes. At small ΔT, lower density, larger, and more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We found that networks composed of chains of equal contour length can have shear moduli that depend strongly on the end-to-end distance even when probed at the same strand concentration. Hence, this shows that even in simple systems the synthesis protocol can have a large impact on the final material properties of the network even when it does not affect the chemical properties of its basic constituents, as recently highlighted in a microgel system …”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…We found that networks composed of chains of equal contour length can have shear moduli that depend strongly on the end-to-end distance even when probed at the same strand concentration. Hence, this shows that even in simple systems the synthesis protocol can have a large impact on the final material properties of the network even when it does not affect the chemical properties of its basic constituents, as recently highlighted in a microgel system …”
Section: Discussionmentioning
confidence: 55%
“…Hence, this shows that even in simple systems the synthesis protocol can have a large impact on the final material properties of the network even when it does not affect the chemical properties of its basic constituents, as recently highlighted in a microgel system. 58 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence this shows taht even in simple systems the synthesis protocol can have a large impact on the final material properties of the network even when it does not affect the chemical properties of its basic constituents, as recently highlighted in a microgel system. 58 We then compared the results from the simulations of the phantom network polymer theory, which was revisited to obtain explicit expressions for the shear modulus assuming three different chain conformation fluctuations, namely the exact freely-jointed chain, Gaussian, and extensible freely-jointed chain models. We observed a non-monotonic behaviour of G as a function of the strand density that, thanks to a comparison with the theoretical results, can be completely ascribed to entropic effects that cannot be accounted for within a Gaussian description.…”
Section: Discussionmentioning
confidence: 99%
“…Freeman and co-workers [35]. At several large scale facilities PCS can be used to follow microgel samples in-situ during small-angle neutron scattering experiments [75,94].…”
Section: Dynamic Light Scattering (Dls/pcs)mentioning
confidence: 99%